Happiness project : or why I spent a year trying to sing in the morning, clean my closets, fight right, read Aristotle, and generally have more fun - Rubin, Gretchen Craft (New York, NY Harper, 2009)
A thoughtful and prescriptive work on happiness filled with practical advice, sharp insight, charm, and humor.
January, Vitality: boost energy -- February, Marriage: remember love -- March, Work: aim higher -- April, Parenthood: lighten up -- May, Leisure: be serious about play -- June, Friendship: make time for friends -- July, Money: buy some happiness -- August, Eternity: contemplate the heavens -- September, Books: pursue a passion -- October, Mindfulness: pay attention -- November, Attitude: keep a contented heart -- December, Happiness: boot camp perfect -- Your happiness project -- Further reading.
95387
Keywords: Happiness; Self-actualization (Psychology)